2019
DOI: 10.1098/rspb.2019.1343
|View full text |Cite
|
Sign up to set email alerts
|

Biased movement drives local cryptic coloration on distinct urban pavements

Abstract: Explanations of how organisms might adapt to urban environments have mostly focused on divergent natural selection and adaptive plasticity. However, differential habitat choice has been suggested as an alternative. Here, we test for habitat choice in enhancing crypsis in ground-perching grasshoppers colonizing an urbanized environment, composed of a mosaic of four distinctly coloured substrates (asphalt roads and adjacent pavements). Additionally, we determine its relative importance compared to present-day na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 51 publications
3
40
0
Order By: Relevance
“…The broader pattern of habitat matching appears to have at least one adaptive function—prey capture. Individuals on well‐matched backgrounds were more likely to be found with prey (Figure b), although manipulative experiments of ambush bug colour are needed to definitively link phenotype‐environment matching to increases in prey capture (Edelaar et al, ). Greater prey capture likely confers increased longevity and reproductive output, increasing fitness and providing an adaptive advantage to phenotype–environment matching.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The broader pattern of habitat matching appears to have at least one adaptive function—prey capture. Individuals on well‐matched backgrounds were more likely to be found with prey (Figure b), although manipulative experiments of ambush bug colour are needed to definitively link phenotype‐environment matching to increases in prey capture (Edelaar et al, ). Greater prey capture likely confers increased longevity and reproductive output, increasing fitness and providing an adaptive advantage to phenotype–environment matching.…”
Section: Discussionmentioning
confidence: 99%
“…Note that while ambush bugs may potentially choose their habitat and alter their phenotype, they are unlikely to modify the colour of their habitats (i.e. the third mechanism described in Edelaar et al, ), and accordingly we have not investigated this potential mechanism of phenotype–environment matching.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Edelaar et al. (2019) showed that grasshoppers inhabiting different anthropogenic substrates have heritable differences in color (matching their various backgrounds), despite being mere meters apart. For natural selection to sustain these differences in such highly mobile organisms would require unrealistically intense selection (∼90% daily mortality rates; Edelaar et al.…”
mentioning
confidence: 99%
“…For natural selection to sustain these differences in such highly mobile organisms would require unrealistically intense selection (∼90% daily mortality rates; Edelaar et al. 2019). Such discrepancies between empirical data and migration‐selection theory suggest that we must sometimes invoke additional processes (Edelaar and Bolnick 2019).…”
mentioning
confidence: 99%